The bioindication importance of the Carabidae communities of Veporské vrchy and Juhoslovanská kotlina - Langraf Vladimír; Petrovičová Kornélia; David Stanislav; Schlarmannová Janka (Ekológia (Bratislava), 2016)
The Carabidae family (Coleoptera) is used frequently for its bioindication potential to detect the environmental burden. In 2013 and 2014, we studied the correlation of Carabidae on the biotopes of six areas in the Veporské vrchy Mts and the Juhoslovenská kotlina basin by using pitfall traps, Möricke plates and Bambara beetle traps. Out of 432 recorded specimens of beetles (53 species, 15 families), the Carabidae family were the highest number of species and specimens represented, with which we confirmed higher anthropogenic interference and disturbance of ecosystems in the Juhoslovenská kotlina basin. This statistic confirms the presence of the following species typically found on arable land: Anchomenus dorsalis, Calathus fuscipes fuscipes, Harpalus affinis and Pseudoophonus rufipes. The ecosystems in the Veporské vrchy Mts region show less disturbance, and the anthropological impact is smaller, indicated by the presence of the Carabus problematicus species, an important indicator of the conservation of natural forest ecosystems.